Prevalence of depressive symptoms and correlates among individuals who self-reported SARS-CoV-2 infection after optimizing the COVID-19 response in China - Wei, Liangjia; Qin, Jiao; Lin, Zhifeng; Huang, Xinju; He, Jinfeng; Yu, Dee; Zhang, Fei; Li, Sisi; Cen, Ping; Li, Mu; Luo, Tong; Zhang, Rongjing; et al. (Frontiers in Public Health, 2024)
Background: The burden of depression symptoms has increased among individuals infected with SARS-CoV-2 during COVID-19 pandemic. However, the prevalence and associated factors of depressive symptoms among individuals infected with SARS-CoV-2 remain uncertain after optimizing the COVID-19 response in China. Methods: An online cross-sectional survey was conducted among the public from January 6 to 30, 2023, using a convenience sampling method. Sociodemographic and COVID-19 pandemic-related factors were collected. The depression symptoms were assessed using the Patient Health Questionnaire-9 (PHQ-9). Logistic regression analysis was performed to explore the associated factors with depressive symptoms. Results: A total of 2,726 participants completed the survey. The prevalence of depression symptoms was 35.3%. About 58% of the participants reported experiencing insufficient drug supply. More than 40% of participants reported that they had missed healthcare appointments or delayed treatment. One-third of participants responded experiencing a shortage of healthcare staff and a long waiting time during medical treatment. Logistic regression analysis revealed several factors that were associated with depression symptoms, including sleep difficulties (OR, 2.84; 95%CI, 2.34-3.44), chronic diseases (OR, 2.15; 95%CI, 1.64-2.82), inpatient treatment for COVID-19(OR, 3.24; 95%CI, 2.19-4.77), with COVID-19 symptoms more than 13 days(OR, 1.30, 95%CI 1.04-1.63), re-infection with SARS-CoV-2 (OR, 1.52; 95%CI, 1.07-2.15), and the increased in demand for healthcare services(OR, 1.32; 95%CI, 1.08-1.61). Conclusion: This study reveals a moderate prevalence of depression symptoms among individuals infected with SARS-CoV-2. The findings underscore the importance of continued focus on depressive symptoms among vulnerable individuals, including those with sleeping difficulties, chronic diseases, and inpatient treatment for COVID-19. It is necessary to provide mental health services and psychological interventions for these vulnerable groups during the COVID-19 epidemic.